∫ 0 4 π ln ( 1 + tan x ) d x = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I = ∫(0,π/4)ln(1 + tanx)dx
I = ∫(0,π/4)ln(1+tan(π/4-x)) dx
= ln(1+(tanπ/4-tanx)/(1+tanπ/4tanx))
= ln (1+(1-tanx)/(1+tanx))
= ln(2/(1+tanx))
On adding, 2I = ∫(0,π/4)ln2 dx
2I =ln2 ∫(0,π/4)dx
I = ((ln2)/2) [x](0,π/4)
I = (πln2)/8
I = ∫ 0 4 π ln ( 1 + t a n x ) d x ( A p p l y i n g ∫ a b f ( x ) d x = ∫ a b f ( a + b − x ) d x ) I = ∫ 0 4 π l n ( 1 + t a n ( 4 π − x ) ) d x = ∫ 0 4 π l n ( 1 + 1 + t a n x 1 − t a n x ) d x = ∫ 0 4 π l n ( 1 + t a n x 1 + t a n x + 1 + t a n x 1 − t a n x ) d x
I = ∫ 0 4 π l n ( 1 + t a n x 2 ) d x = ∫ 0 4 π l n 2 − l n ( 1 + t a n x ) d x = ∫ 0 4 π l n 2 d x − ∫ 0 4 π l n ( 1 + t a n x ) d x = l n 2 [ 4 π ] − I 2 I = 4 π l n 2 I = 8 π l n 2
Problem Loading...
Note Loading...
Set Loading...
There are a couple ways to do this (manipulating with sum to product formulas was one way a friend used) but this is my preferred method.
I = ∫ 0 4 π ln ( 1 + tan x ) d x
We can use the special case of the identity ∫ a b f ( x ) d x = ∫ a b f ( a + b − x ) d x saying that ∫ 0 k f ( x ) d x = ∫ 0 k f ( k − x ) d x .
f ∫ 0 4 π ln ( 1 + tan x ) d x = ∫ 0 4 π ln ( 1 + tan ( 4 π − x ) ) d x = ∫ 0 4 π ln ( 1 + 1 + tan 4 π tan x tan 4 π − tan x ) d x = ∫ 0 4 π ln ( 1 + 1 + tan x 1 − tan x ) d x = ∫ 0 4 π ln ( 1 + tan x 1 + tan x + 1 + tan x 1 − tan x ) d x = ∫ 0 4 π ln ( 1 + tan x 2 ) d x = ∫ 0 4 π ln 2 − ln ( 1 + tan x ) d x = ∫ 0 4 π ln 2 d x − ∫ 0 4 π ln ( 1 + tan x ) d x = 4 π ln 2 − I
Bringing the I to the left side, we find that 2 I = 4 π ln 2 ⇒ I = 8 π ln 2